Multicriterial approach to the determination of buffer zones for the Moravian Karst protected landscape area in the Czech Republic - Malá, Jitka; Hrich, Karel; Vaculíková, Klára; Lejska, Stanislav (Environmental monitoring and assessment, 2022)
Allogenic recharge is an important source of pollution affecting karst protected terrains. In order to prevent the introduction of contaminants and the deterioration of karst phenomena, it is necessary to determine buffer zones that require protection, which is sometimes difficult, especially in densely populated areas. A multicriterial approach for the determination of buffer zones was proposed and verified. The method combines two criteria to identify those watercourses whose catchments lying outside the protected area need to be protected, namely the water quality index and the mass flow of pollutants. The case study was performed in the Moravian Karst (Czech Republic), which is fed by more than 10 small allogenic watercourses. The study proved that not only water quality, but also mass flow of pollutants conditioned by watercourse discharge must be considered. This approach can be adapted for all types of protected landscape areas with water pollution originating in surrounding areas.
Keywords: Allogenic watercourses; Water Pollutants, Chemical; kvalita vody; Environmental Monitoring; Mass flow of pollutants; Water quality index; Water Pollution; monitorování životního prostředí; znečištění vody; Organic pollution; Nutrients; Karst protection; Česká republika; Water Quality; chemické látky znečišťující vodu; Czech Republic